Formative Assessment in Immersive environments: a Semantic Approach to automated Evaluation of User Behavior in Open Wonderland - Maderer, J.; Guetl, Christian; AL-Smadi, M. (Immersive Education Org, 2013)
This paper proposes a pedagogic-prominent approach to design automated assessment and feedback apart from the 3D virtual worlds and use them to support guided learning. Through an externalization of the assessment process, the approach supports interaction between educators and virtual environment designers, allowing pedagogic content to be identified at the development stage and then manipulated dynamically in response to learner actions and interactions within an overarching set of pedagogic goals defined by the educator or trainers. The method supports integration with automated assessment technologies, allowing such tools to recognise and respond immediately to learner actions by modifying the virtual environment or triggering feedback. This decoupling between the assessment engine and the 3D virtual worlds enables supporting a variety of environments as well as different contexts and application domains.